2018
DOI: 10.1155/2018/4160570
|View full text |Cite
|
Sign up to set email alerts
|

Poroelasticity and Fluid Flow Modeling for the 2012 Emilia-Romagna Earthquakes: Hints from GPS and InSAR Data

Abstract: The Emilia-Romagna seismic sequence in May 2012 was characterized by two mainshocks which were close in time and space. Several authors already modeled the geodetic data in terms of the mechanical interaction of the events in the seismic sequence. Liquefaction has been extensively observed, suggesting an important role of fluids in the sequence. In this work, we focus on the poroelastic effects induced by the two mainshocks. In particular, the target of this work is to model the influence of fluids and pore-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Meanwhile, large vertical deformation is more directly related to the inverse of the coseismic head change. These relationships are consistent with those observed in other postseismic poroelastic studies (Albano et al, 2017;Nespoli et al, 2018) The overall pattern of the horizontal postseismic poroelastic displacement, shown in Figure 1b, is in the opposite direction of the fluid flow during poroelastic relaxation. This is contrary to the behavior observed around pumping wells, where horizontal displacements are generally in the direction of fluid flow and hence towards minima in head (Wang, 2000).…”
Section: Patterns In Initial and Total Poroelastic Responsesupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, large vertical deformation is more directly related to the inverse of the coseismic head change. These relationships are consistent with those observed in other postseismic poroelastic studies (Albano et al, 2017;Nespoli et al, 2018) The overall pattern of the horizontal postseismic poroelastic displacement, shown in Figure 1b, is in the opposite direction of the fluid flow during poroelastic relaxation. This is contrary to the behavior observed around pumping wells, where horizontal displacements are generally in the direction of fluid flow and hence towards minima in head (Wang, 2000).…”
Section: Patterns In Initial and Total Poroelastic Responsesupporting
confidence: 91%
“…Poroelastic deformation is thought to occur on timescales of days to weeks, whereas longer timescales on the order of months to years are associated with afterslip and viscous relaxation (Barbot & Fialko, 2010;Helmstetter & Shaw, 2009;Freed et al, 2017;Perfettini & Avouac, 2004). However, postseismic poroelastic deformation can occur on multiple timescales that overlap with those currently linked to afterslip and viscous relaxation (Hughes et al, 2010;McCormack & Hesse, 2018;Nespoli et al, 2018). Thus, attributing surface deformation to these different processes may be more complicated than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, fluid diffusion‐related phenomena should propagate with the square of time (e.g., Ross et al, ). It has also been shown that most of the pore fluid dynamics occur in the shallowest layers in the Emilia seismic sequence (Nespoli et al, ) and that, in general, the permeability should considerably decrease with depth (e.g., Ingebritsen & Manning, ). All these considerations led to exclude the fluid diffusion as a dominant triggering mechanism for the aftershocks migration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this aspect is still controversial. Nespoli et al () show that the pore fluid dynamics occur in the shallowest layers (i.e., less than 3.3‐km deep); at greater depths, the permeability is lower and the fluid flow is not sufficient to drain the rock. They model the influence of fluids and pore pressure changes on surface displacements and on the CFF in a 3‐D half‐space and obtain small postseismic pore pressure and CFF changes on the Mirandola fault plane that exclude fluid migration as a primary triggering mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid diffusion after large earthquakes alters crustal stresses and can facilitate subsequent events. This phenomenon has been described by a posteriori complex models that can quantify the stress perturbations and assess the time required for pore fluids to return to hydrostatic conditions (Albano et al, ; Antonioli et al, ; Jónsson et al, ; Malagnini et al, ; Nespoli et al, ; Tung & Masterlark, ; Tung et al, ). The extent of the pore pressure perturbation and the flow recovery time depend on the modeling approach and parameters.…”
Section: Methodsmentioning
confidence: 99%